Balancing ethical norms and duties for the introduction of new medicines through conditional marketing authorization: a research agenda - Maksimova, Mariia V.; van Thiel, Ghislaine J. M. W.; Tromp, Yke; Lechner, Rosan; van Delden, Johannes J. M.; Bloem, Lourens T. (Frontiers in Medicine, 2024)
The European Medicines Agency's conditional marketing authorization (CMA) aims to expedite access to medicines for unmet medical needs by shifting part of the drug development process post-authorization. We highlight ethical issues surrounding CMA: i) complexity of defining unmet medical need; ii) poor understanding of CMA and its impact on informed consent; iii) hope versus unrealistic optimism; iv) implications of prolonged post-authorization studies and potential patient harm; v) rights and duties of patients surrounding participation in post-authorization studies; vi) access to previously authorized CMA medicines; vii) the 'benefit slippage' phenomenon, defined as the gradual shift of strict criteria to less strict criteria. We propose a comprehensive research agenda to address these ethical issues, and stress the need for multi-stakeholder engagement to ensure patient-centered use of CMA.